1990
DOI: 10.1111/j.1751-0813.1990.tb03020.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of inspection procedures for the detection of tuberculous lesions in cattle

Abstract: The sensitivity of the abattoir inspection procedure introduced for Australian export beef in 1976 was compared to a detailed necropsy procedure for the detection of tuberculous lesions in cattle. In a sample of cattle that were reactors to the tuberculin test, abattoir inspection failed to detect an estimated 47% of cattle with lesions. The detailed necropsy examination of cattle with lesions of tuberculosis identified 21 sites of infection compared with 13 to 18 in cattle examined by routine meat inspection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
4
18

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(128 citation statements)
references
References 0 publications
10
92
4
18
Order By: Relevance
“…Apart from light infections, another reason may be an improvement in human and livestock hygiene in some communities. Similar to missed cysticerci lesions at slaughter, an Australian investigation showed that the abattoir necropsy procedure failed to detect an estimated 47.0 % of cattle with TB 5 . The failure to detect single lesions during abattoir inspection, therefore, poses a health risk to consumers, especially when meat is eaten undercooked, in that most measle-or TB-infected carcasses may be passed untreated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from light infections, another reason may be an improvement in human and livestock hygiene in some communities. Similar to missed cysticerci lesions at slaughter, an Australian investigation showed that the abattoir necropsy procedure failed to detect an estimated 47.0 % of cattle with TB 5 . The failure to detect single lesions during abattoir inspection, therefore, poses a health risk to consumers, especially when meat is eaten undercooked, in that most measle-or TB-infected carcasses may be passed untreated.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of recording a group of mycobacterium species causing similar lesions to those of tuberculosis as seen in this study for the purpose of meat inspection sometimes has the effect of inflating the real occurrence of the disease 12 . A thorough systematic necropsy is more likely to detect infection than routine slaughter inspection of carcases 5 . Because of the non-specific nature of granulomas, the tubercle-like lesion is used as a surrogate test at abattoirs.…”
Section: Discussionmentioning
confidence: 99%
“…2b). Given that an infected animal shows visible lesions detectable post mortem, the awareness and the accuracy of the meat inspector is a crucial point for the sensitivity of this SSC [2,11]. Because bTB is a zoonosis and can be transmitted from cattle to people, human Mycobacterium bovis cases are indications of the presence of infected cattle.…”
Section: Passive Sscmentioning
confidence: 99%
“…the ability to detect an outbreak as soon as possible. According to the World Animal Health Organization (Office International des Epizooties, OIE), a surveillance system is a method of surveillance that may include one or more component activities that generates information on the health, disease or zoonosis status of animal populations 2 . The power of a surveillance system to detect cases can also be referred to as its sensitivity and can be estimated when the sensitivities of the surveillance system components are known.…”
Section: Introductionmentioning
confidence: 99%
“…Considerando-se que 58% dos animais infectados com tuberculose apresentam lesões únicas (Corner et al,1990), a inspeção mais detalhada de linfonodos, incluindo os da cabeça, torácicos, mesentéricos Figura 1. Lesões nodulares típicas de tuberculose em órgãos e carcaça de bovinos positivos no teste cervical comparativo.…”
Section: Introductionunclassified